Glencoe medical assisting a patient-centered approach to administrative and clinical competencies - Ramutkowski, Barbara; Barrie, Abdulai; Keller, Cindy; Dazarow, Laurie; Abel, Cindy ([S.l.] : Career Education, 1997)
Glencoe Medical Assisting: A Patient-Centered Approach to Administrative and Clinical Competencies is designed to help students acquire the competence and confidence to master a variety of medical assisting skills, while keeping the patient's emotional well-being at the center of the care they deliver. All of the step-by-step procedures are fully illustrated so students can learn proper techniques. A variety of features help students deal with such complicated issues as educating the patient and treating patients with special needs.
Keywords: medicine,physician assistant